A study on the antecedents and outcomes of using an organization Social Networking Service - Na, BiNaRee; Tak, JinKook (Korean Journal of Industrial and Organizational Psychology, 2013)
The purpose of this study was to analyze antecedents and outcome variables of using an organization social networking service. Data were collected from 314 workers. The results of this study showed that as antecedents innovative culture, learning organization, relationship orientation, and curiosity were significantly related to social networking Service use. Also, social networking service use was significantly related to all the outcome variables such as organizational communication, team cohesion, work intensity, and social networking service stress. Finally, the implications and limitations of this study, and the directions for future research were discussed.